CRISPR‐Based Targeted Epigenetic Editing Enables Gene Expression Modulation of the Silenced Beta‐Galactoside Alpha‐2, 6‐Sialyltransferase 1 in CHO Cells. Issue 10 (11th June 2018) - Marx, Nicolas; Grünwald‐Gruber, Clemens; Bydlinski, Nina; Dhiman, Heena; Ngoc Nguyen, Ly; Klanert, Gerald; Borth, Nicole
Abstract : Despite great efforts to control and modify gene expression of Chinese Hamster Ovary (CHO) cells by conventional genetic engineering approaches, i.e. overexpression or knockdown/‐out, subclonal variation, induced unknown regulatory effects as well as overexpression stress are still a major hurdle for efficient cell line engineering and for unequivocal characterization of gene function. The use of epigenetic modulators – key players in CHO clonal heterogeneity – has only been marginally addressed so far. Here, we present the application of an alternative engineering strategy in CHO cells by utilizing targeted epigenetic editing tools that enable the turning‐on or ‐off of genes without altering the genomic sequence. The present, but silent beta‐galactoside alpha‐2, 6‐sialyltransferase 1 (ST6GAL1) gene is activated by targeting the catalytic domain (CD) of Ten‐Eleven Translocation methylcytosine dioxygenase 1 (TET1) via deactivated Cas9 (dCas9) to its methylated promoter. Stable upregulation in up to 60% of transfected cells is achieved over a time span of more than 80 days. No difference in growth and recombinant protein productivity is observed between activated and control cultures. Re‐silencing by targeted methylation via DNA methyltransferase (DNMT) 3A‐CD resulted in an up to 5.4‐fold reduction of ST6GAL1 mRNA expression in ST6GAL1 expressing cells. This proof‐of‐concept demonstrates the feasibility of using epigenetic editing tools to efficiently modulate gene expression and provide a promising complement to conventional genetic engineering in CHO cells. Abstract : Within the epigenetic mechanisms that control gene expression in CHO cells, DNA methylation of promoters is associated with silencing of the corresponding gene. In this study, targeted demethylation of the highly methylated ST6GAL1 promoter with a repurposed CRISPR system transcriptionally activated the beforehand silent gene. The long‐lasting effect can be reversed by targeted re‐methylation of the ST6GAL1 promoter, which demonstrates the great potential of targeted epigenetic editing tools for detailed gene‐of‐function studies as well as for cell engineering approaches.